Application of Narrative Counseling to Reduce Communication Apprehension in Junior High School Students - Sekar Kurnia Rahmadani; Netrawati; Zadrian Ardi (Journal Of Psychology, Counseling And Education, 2024)
This study aims to test the application of narrative counseling to reduce students' communication anxiety. The counseling process consists of 3 stages, namely externalization of problems, Mapping the influence of problems in a person's life and Mapping the influence of a person's life on the development of problems. This study used a pre-test post-test one group design. The subjects of this study were 5 students who experienced high communication anxiety. Data analysis of this study used non-parametric statistics of the sign test and IMCS. The results of the data analysis showed that ρ = 0.031 was smaller than α = 0.05. Thus H0 was rejected and Ha was accepted, so the accepted hypothesis was that there was a decrease in communication anxiety scores in junior high school students after narrative counseling was given. While the results of the IMCS analysis showed the emergence of different actions, reflections, protests, reconceptualizations and changes before the narrative counseling intervention. This means that the application of narrative counseling can reduce communication anxiety in junior high school students.